"It Was . . . the Word 'Scrotum' on the First Page": Educators' Perspectives of Controversial Literature. (September 2019) - Kimmel, Sue C.; Hartsfield, Danielle E.
Preemptive censorship occurs when educators avoid particular books because they dislike the ideas or values the books contain or fear the controversy the books may evoke. Although not as blatant as other forms of censorship, preemptive censorship has the unfortunate consequence of restricting children's access to ideas and information. Moreover, preemptive censorship violates students' intellectual freedom and right to read. In this study, we employ critical discourse analysis to examine discussions by preservice teachers and school librarians as they responded to a controversial children's book. Our analysis of the discussions revealed that many preservice educators maintain a protective view of children, fear the negative reactions of parents, and would choose to engage in preemptive censorship rather than create controversy in their classrooms and schools. We conclude by recommending ways that teacher educators can support preservice teachers and school librarians in their efforts to promote the professional value of intellectual freedom.